Devenir chercheur ou enseignant chercheur : le goût pour la recherche des doctorants à l’épreuve du marché du travail - Claire Bonnard; Julien Calmand; Jean-François Giret (Recherches en Éducation)
Doing a PhD to become a researcher or an assistant-professor is often considered as a difficult and risky career. In France, PhD graduates experience greater difficulties than in other OCDE countries to find a stable position in the labour market. Our research examines the reasons that lead young people to enroll in a doctoral program, to choose an academic career and finally, to find a tenured job. Using a survey implemented by the Cereq on university leavers, our results show that the “taste” for research they have when they enter in higher education and their social capital strongly influence their academic and professional careers. However, variables related to the general situation on the labor market will also influence young people’s trajectories.